Cost-Utility Analysis of Rosuvastatin (20 mg) to Prevent Cardiovascular Diseases in Iran - Aziz Rezapour; Abdosaleh Jafari; Hamid Talebianpour (Advanced Biomedical Research, 2024)
Background: Cardiovascular diseases are a main cause of disease burden in developing and developed countries. This study aimed to evaluate the cost-utility of rosuvastatin 20 mg in contrast with no intervention for the prevention of cardiovascular disease in Iran. Materials and Methods: The costs and utility of rosuvastatin 20 mg were compared to nonintervention in patients with cardiovascular disease for the whole lifetime horizon in this study using the Markov model. Cost and utility data were taken from literature. After estimating the incremental cost-effectiveness ratio, a sensitivity analysis was performed using TreeAge Pro 2011 software to cope with uncertainty. Results: Based on finding, the expected cost and quality-adjusted life years (QALYs) of using rosuvastatin 20 mg were $300 and 12, and the values for no intervention were $56 and $10, respectively. Given the threshold of $20800, using rosuvastatin 20 mg was cost-effective compared to no intervention and the incremental cost was $122 per QALY. The results showed that the highest costs were related to admission to the coronary care unit (CCU) ward. Moreover, among the costs of paraclinical services, the highest were those of echocardiography. Furthermore, Troponin accounted for most of the cost of laboratory tests. Conclusion: It is recommended that policymakers consider using rosuvastatin 20 mg by cardiologists while designing clinical guidelines for the diagnosis of patients with cardiovascular diseases. Because of the high cost of cardiovascular diseases in Iran, it is suggested that policymakers should consider cost control strategies to impose lower costs on patients.